Rata, Matiu Waitai - McDowell, Tiopira (2020)
Keywords: biography; mana motuhake; ratana; tino rangatiratanga; waitangi tribunal

Recession hits Māori and Pasifika harder. They must be part of planning New Zealand's COVID-19 recovery - Moewaka Barnes, Helen; Kukutai, Tahu; McCreanor, Tim; Mcintosh, Tracey (The Conversation, 2020)
Māori knowledge, memory and cultural strength will only enhance New Zealand’s economic recovery planning – if they are listened to.
Keywords: covid-19; crown policy; discrimination; treaty obligations